PERFORMA AYAM KAMPUNG UNGGUL BALITNAK (KUB) YANG DIBERI TEPUNG LARVA BLACK SOLDIER FLY (BSF) (Hermetia Illucens) SEBAGAI PENGGANTI TEPUNG IKAN DALAM RANSUM: PERFORMANCE OF BALITNAK SUPERIOR LOCAL (KUB) CHICKENS FED BLACK SOLDIER FLY (HERMETIA ILLUCENS) LARVAE MEAL AS A SUBSTITUTE FOR FISHMEAL (Jurnal Peternakan Nusantara, 2022)
KUB chicken is native Indonesian chicken resulted from crossbreeding program conducted by Indonesian Research Institute for Animal Production (Balitnak). Feed is one of the factors that determine chicken farming productivity. The cost of commercial feed is relatively high. Black soldier fly larvae meal is potential alternative which can be used to substitute fishmeal which is one of the most expensive ingredients used in commercial feed. BSF larvae meal contains 40.2% crude protein, 28% crude fat, 2.36% calcium, and 0.88% phosphorus. This study was aimed at assessing the performance of KUB chickens fed BSF larvae meal used as the substitute for fishmeal in ration. The study was conducted within 75 days from 1 April to 15 June 2021 at Nambo Peuntas, Suka Jaya Village, Taman Sari District, Bogor Regency. One-hundred KUB chickens aged 1 day with average body weight of 29.77±2.94 were allocated evenly into 20 experimental cage units in a completely randomized design with 5 treatments and 4 replicates. Treatment consisted of rations containing 0% BSF larvae meal + 10 % fishmeal (R0), 2.5% BSF larvae meal + 7.5 % fishmeal (R1), 5% BSF larvae meal + 5% fishmeal (R2), 7.5% BSF larvae meal + 2.5% fishmeal (R3), and 10% BSF larvae meal + 0 % fishmeal (R4). Results showed that no significant differences (P>0.05) in the performance of KUB chickens were found. It was concluded that BSF larvae meal could be used to substitute the whole fishmeal in rations of KUB chickens without any detriment to the chicken performance.